Association of Physical Activity Intensity and Light/Deep Sleep in Young People from Southern Spain - Pablo Ramírez-Espejo; José Luis Solas-Martínez; Manuel J. de la Torre-Cruz; Alberto Ruiz-Ariza (Children)
Background: Previous research has examined the relationship between physical activity (PA) and sleep quality in young people. However, studies exploring how different intensities of PA relate to light and deep sleep, using objective measurement tools, remain scarce. Therefore, the aim of the present study was to analyze the potential associations between PA intensity and sleep stages and to determine the most effective intensity of PA for positively influencing sleep during adolescence. Methods: The sample consisted of 1072 Spanish pre-adolescents and adolescents (53% girls and 47% boys) aged 13.03 ± 1.79 years. Sleep and intensity of PA were measured using the Xiaomi Mi Band 4 smartband. Sleep was categorized as light or deep, while PA intensity was determined by heart rate (HR) and classified as light (resting to 50% of maximum HR), moderate (50–70% of max HR), and vigorous (70–85% of max HR). Results: Analyses revealed that greater daily time spent in light-intensity PA was associated with less light sleep and more deep sleep. Additionally, vigorous-intensity PA was positively associated with increased deep sleep. No negative associations were observed between moderate-intensity PA and sleep quality. In conclusion, this study suggests that promoting prolonged light-intensity activities (e.g., walking) or short bursts of vigorous activity (e.g., sports participation) may enhance sleep quality during pre-adolescence and adolescence.